O papel da mulher no contexto das agroindústrias rurais e do artesanato de Faxinal do Soturno/RS – Brasil: trabalho, renda e autonomia - Fantineli, Dreisse Gabbi (2021)
This research refers to a study about the important role that women have in the rural area, role which is usually not well regarded and it is considered as “help”. The general objective of this research is to understand the role of family farming in generating income within the productive unit, from agroindustries’ work and handcraft activity in the town of Faxinal de Soturno – RS. In order to achieve the proposed objective, natural, social economic aspects of the aforementioned town were researched. Thereafter, the theoretical framework and the research instrument were constructed in the form of interviews. The target participants of this study are family farmers from the town of Faxinal do Soturno/RS. However, in order to develop this investigation, the extension worker, the technician from Emater, the secretary of agriculture and the coordinator of tourism and culture from Faxinal do Soturno/RS also participated in the research. In the town, there are seven agroindustries that are managed by women who contribute to generate income and to value women’s work in the family unit. There is, also, a group of artificers who produce their handcraft in order to sell in regional and local markets to generate income and as a result, their self-esteem increases. By the end of the study, it was possible to verify that both agroindustry and handcraft contribute to generate income for these women. This income is used to pay household expenses and it supports the family and also helps to boost their self-esteem, that is, another incentive for these women to increasingly expand their autonomy. Therefore, it is necessary and important that public policies related to family farming be created so these women can have opportunities and support, in addition to being protagonists of their work.